Effect of UV-B radiation on physiological and phenological plasticity in rice (Oryza sativa L.) - Wagh Yogesh Sahebrao (Department of plant physiology, College of horticulture, 2015)
A global depletion of the stratospheric ozone layer, largely due to the release of pollutant such as chlorofluorocarbons (CFCs) caused by human activities, has resulted in an increase of solar Ultraviolet-B (UV-B) radiation in the range of 280-320 nm at the earth’s surface. Elevated UV-B exposure causes temporary or irreversible damage to plant growth and development. Though UV-B is only a minor component of total solar radiation (less than 0.5%), due to its high energy, its potential for causing biological damage is very high. UV-B radiation is highest in tropical region where rice is grown as the major food crop in these regions. Decline in rice yield during puncha season (Dec-March) gives an indication on the effect of UV-B radiation on rice yield. Failure of rice crop in puncha season has lead to abandoning of double cropping in productive rice ecosystem like kole lands of Kerala. This needs detailed investigations to come up with realistic recommendations to overcome such situations. Therefore, the present study was conducted to understand the effect of UV-B radiation on morphological, physiological, phenological and biochemical changes in rice (Oryza sativa L.). The experiment was conducted in pot culture during December 2013-April 2014, with two varieties Jyothi and Uma under three different levels of UV-B radiation i.e. - natural solar UV-B condition where crops were exposed to 100% natural solar radiation (T1), reduced UV-B radiations using UV-B Mylar film which measures UV-B as zero (T2) and 85% ambient radiation including UV-B + UV-B supplemented with UV-B lamps in polyhouse (T3). The results indicated that UV-B radiation, in the range of 1.30 to 3.58 Wm2, during the study period affected the productivity of the crop. There was significant variation in UV-B radiation from 10 am to 4 pm in all the months throughout the growing period and the maximum value was recorded during the month of March, 2014. The highest crop yield was recorded in UV-B excluded condition (T2). This was due to more No. of spikelet per panicle, filled grain per panicle and 1000 grain weight. High photosynthetic rate, stomatal conductance and more canopy cooling at both vegetative and reproductive phases, along with more IAA content, total chlorophyll and chlorophyll ‘a’ have contributed the high yield in T2 condition. The increase in physiological parameters like photosynthetic rate, stomatal conductance and canopy cooling; morphological traits like flag leaf angle and panicle length and biochemical constituents like Chlorophyll ‘a’, total chlorophyll and IAA content observed under UV-B excluded condition (T2) positively favoured the high yield and harvest index in the present study. Though the crop grown under natural solar radiation expressed more No. of productive tillers per hill, it could not produce more No. of spikelet and filled grain per panicle. Instead it produced more amount of flavanoid and phenol content by channelizing the photo assimilates at flowering stage. The phenophases of the crop like days to heading, 50% flowering and days to harvestable maturity were delayed by 4-5 days under open condition (T1).The varieties Jyothi and Uma could not produce significant difference in yield. In the present study decrease in yield and yield attributes were observed due to the current level of natural solar UV-B radiation. The UV-B radiation under open condition restricted filling of grain and further grain development leading to lesser number of filled grains per panicle and thousand grain weight.